NPAS2 Regulation of Anxiety-Like Behavior and GABAA Receptors - Ozburn, Angela R.; Kern, Joseph; Parekh, Puja K.; Logan, Ryan W.; Liu, Zheng; Falcon, Edgardo; Becker-Krail, Darius; Purohit, Kush; Edgar, Nicole M.; Huang, Yanhua; McClung, Colleen A. (Frontiers in Molecular Neuroscience, 2017)
Abnormal circadian rhythms and circadian genes are strongly associated with several psychiatric disorders. NPAS2 is a core component of the molecular clock that acts as a transcription factor and is highly expressed in reward- and stress-related brain regions such as the striatum. However, the mechanism by which NPAS2 is involved in mood-related behaviors is still unclear. We measured anxiety-like behaviors in mice with a global null mutation in Npas2 (Npas2 null mutant mice) and found that Npas2 null mutant mice exhibit less anxiety-like behavior than their wild-type littermates (in elevated plus maze, light/dark box, and open field assay). We assessed the effects of acute or chronic stress on striatal Npas2 expression, and found that both stressors increased levels of Npas2. Moreover, knockdown of Npas2 in the ventral striatum resulted in a similar reduction of anxiety-like behaviors as seen in the Npas2 null mutant mouse. Additionally, we identified Gabra genes as transcriptional targets of NPAS2, found that Npas2 null mutant mice exhibit reduced sensitivity to the GABAa positive allosteric modulator, diazepam and that knockdown of Npas2 reduced Gabra1 expression and diazepam responses in the ventral striatum. These results 1) implicate Npas2 in response to stress and the development of anxiety, and 2) provide functional evidence for the regulation of GABAergic neurotransmission by NPAS2 in the ventral striatum.